Order of Magnitude Increase in Storage Time of Photonic-Phononic Memory - Becker, Steven; Geilen, Andreas; Stiller, Birgit (2023 International Conference on Photonics in Switching and Computing, PSC 2023, 2023)
With the recent developments in photonic computing platforms, the need of novel optical memories becomes increasingly important. Optoacoustic memories have shown great potential due to their quick access time, coherent nature, and broad bandwidth. These continuously tunable memories can be controlled entirely optically, but so far their intrinsic storage time is limited by the acoustic life time to approximately 10 ns. In this work, we experimentally demonstrate a cryogenic optoacoustic memory with an intrinsic storage time beyond 135 ns.
CRIS-Team Scopus Importer:2023-12-15
Keywords: nonlinear optics; Optical computing; optical memory; stimulated Brillouin scattering